2021
DOI: 10.1111/hsc.13294
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and intention to leave among care workers in residential care homes in Hong Kong: Technology acceptance as a moderator

Abstract: Care workers in residential care settings for older adults often experience job burnout, resulting in a high turnover rate. Previous studies offered contradictory findings on technology use in the workplace and its relationship with burnout. This study aimed to explore the moderator role technology acceptance plays in the relationship between burnout and intention to leave among care workers in residential care settings in Hong Kong. The study was based on a multicenter, cross-sectional questionnaire survey. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Fifteen articles were retained for analysis (Table 2). [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Studies reported in the articles were conducted in several countries and employed a variety of quantitative, qualitative, and mixed methodologies. Technologies examined in the articles were of 3 general types: physical or mobility aids, sensor and monitoring systems, and socialization enhancement technologies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fifteen articles were retained for analysis (Table 2). [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Studies reported in the articles were conducted in several countries and employed a variety of quantitative, qualitative, and mixed methodologies. Technologies examined in the articles were of 3 general types: physical or mobility aids, sensor and monitoring systems, and socialization enhancement technologies.…”
Section: Resultsmentioning
confidence: 99%
“…The articles reported the results of studies in 9 countries. The United States of America, 32 , 33 Australia, 42 , 45 Canada, 35 , 36 France, 38 , 39 Hong Kong, 43 , 46 and the United Kingdom 37 , 40 were sites reported in 2 articles each. Japan, 44 the Netherlands, 41 and Thailand 34 were sites reported in 1 article each.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations